2023
DOI: 10.1021/acs.est.3c07722
|View full text |Cite
|
Sign up to set email alerts
|

The Futility of Relative Methane Reduction Targets in the Absence of Measurement-Based Inventories

Bradley M. Conrad,
David R. Tyner,
Matthew R. Johnson

Abstract: Under the Global Methane Pledge, Canada is developing oil and gas sector methane regulations targeting 75% reductions from 2012 levels by 2030. Without measured baselines and inventories, such policies are ultimately unverifiable and unenforceable. Using the major oil and gas producing province of Saskatchewan as a case study, we derive first-ever measurement-based methane inventories for the region and comprehensively model previous emissions back to the 2012 baseline. Although relative reductions of 23–69% h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…As shown in Figure , the site-level emission rates for CHOPS facilities in Alberta have decreased from 2018 to 2021, indicating regulatory impacts in mitigating CHOPS emissions in Alberta. However, despite regulatory efforts, results from the aerial surveys conducted in 2018, 2020, and 2021 showed no significant difference in emission rates in Saskatchewan. While Saskatchewan has declared to have met its 2025 reduction target based on inventory estimates, uncertain baselines, underreported emissions, decreased production, and lack of measurement data preclude a definitive conclusion regarding the efficacy of recent regulations. , Of particular concern is the potential for significant, often underestimated CH 4 emissions from CHOPS operations in Saskatchewan, , which may not have received adequate attention during the implementations of CH 4 reduction regulations.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Figure , the site-level emission rates for CHOPS facilities in Alberta have decreased from 2018 to 2021, indicating regulatory impacts in mitigating CHOPS emissions in Alberta. However, despite regulatory efforts, results from the aerial surveys conducted in 2018, 2020, and 2021 showed no significant difference in emission rates in Saskatchewan. While Saskatchewan has declared to have met its 2025 reduction target based on inventory estimates, uncertain baselines, underreported emissions, decreased production, and lack of measurement data preclude a definitive conclusion regarding the efficacy of recent regulations. , Of particular concern is the potential for significant, often underestimated CH 4 emissions from CHOPS operations in Saskatchewan, , which may not have received adequate attention during the implementations of CH 4 reduction regulations.…”
Section: Resultsmentioning
confidence: 98%
“…As with most other well types, casing pressure must be relieved to avoid restricting oil production and to avoid pushing the liquid column down to the point where gas enters the pump and leads to cavitation and motor failure . Thus, the potential sources of CH 4 emissions from a CHOPS facility includes the release of casing gas from an annular vent, engine shed vents, failing pneumatics, flashing losses, breathing losses from storage tanks, truck loading emissions as well as fugitive leakage including leaking connectors and valves. ,, Emissions can also arise from abandoned or suspended CHOPS wells. Casing gas can be utilized as fuel for the engine, and studies have reported that a large portion of total site emissions in Lloydminster was from sheds containing fuel gas engines. ,, …”
Section: Introductionmentioning
confidence: 99%
“…We also tested the performance of Bridger Photonics’ Gas Mapping LiDAR, an aircraft-based remote sensing system that quantifies observed plume emissions. , The use of this technology has proliferated in Canada to quantify upstream oil and gas methane emissions ,,, and has been supported by federal and provincial Canadian governments. Using POD curves from Conrad et al (175-m altitude, 3-m/s wind speed), we found that only the largest 7% of emitters, representing 47% of methane emissions, are expected to be detected in Alberta (<2% of emitters and 44% of emissions in B.C.).…”
Section: Resultsmentioning
confidence: 99%
“…Simple calculations or infrequent measurement can lead to considerable uncertaintyand often underestimationfor many emission sources. While recent work has shed new light on emissions from on-site compressors, liquid storage tanks, and heavy oil production, wellbore leakage remains understudied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation